THE ROLE OF BRAND IMAGE MEDIATES THE EFFECT OF PRODUCT QUALITY ON REPURCHASE INTENTIONS AT KEDAI JUKUNG JEMBRANA - Ni Nyoman Estirina Priyandari; I Made Wardana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The development of the culinary business shows an increase every year. This is indicated by the increasing number of restaurants and restaurants. According to data from the Badan Pusat Statistik Provinsi Bali, in 2023 there were 4.429 units of restaurants and eateries spread across various districts in Bali. This figure increased from 2022 which only amounted to 3.245 units. Jembrana Regency shows an increasing number of restaurants and eateries every year. The increasing number of restaurants and eateries in Jembrana Regency has resulted in increasingly fierce competition. One of the restaurants in Jembrana Regency is Kedai Jukung. This restaurant serves various types of menus, such as western to local dishes. This study aims to determine the role of brand image in mediating the effect of product quality on repurchase intentions at Kedai Jukung in Jembrana. This research was conducted with a quantitative approach. The sample used was 120 respondents with the sampling technique, namely non probability sampling with purposive sampling method. The data collection technique used a questionnaire in the form of a Google Form which had been tested for validity and reliability. Data analysis techniques using path analysis and sobel test. The results showed that: (1) product quality has a positive and significant effect on brand image at Kedai Jukung in Jembrana; (2) product quality has a positive and significant effect on repurchase intention at Kedai Jukung in Jembrana; (3) brand image has a positive and significant effect on repurchase intention at Kedai Jukung in Jembrana; (4) brand image is able to mediate the effect of product quality on repurchase intention at Kedai Jukung Jembrana. The theoretical implications of this research are to strengthen and develop previous research and add to empirical studies on product quality, brand image, and repurchase intentions. While the practical implications of this research are that it can be a reference for Kedai Jukung to pay more attention to and maximize product quality and as a reference to be able to improve Kedai Jukung brand image so that consumer repurchase intentions can increase.